PENGARUH PENGETAHUAN MEREK, PERSEPSI KUALITAS DAN INOVASI KONSUMEN TERHADAP SIKAP PADA PERLUASAN MEREK DETTOL DAN LIFEBUOY DI TIP TOP RAWAMANGUN - Rizan, Mohammad; Fitri, Wita Nuranindya; Kresnamurti R. P., Agung (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
The purpose of the research areto describe brand knowledge, perceived quality and consumer innovativeness toward brand extension attitude, to test the influence of brand knowledge toward brand extension attitude, to test the influence of perceived quality toward brand extension attitude, to test the influence of consumer innovativeness toward brand extension attitude, to test the influence of brand knowledge, perceived quality and consumer innovativeness toward brand extension attitude simultaneously. The methods of research are descriptive and causal, with regression analysis and testing with SPSS software.The sample of the research isTip Top Rawamangun’s customers who use Dettol but had been used Lifebuoy Previously. The results of the t test shows brand knowledge significantly influence brand extension attitude on Dettol and Lifebuoy. Perceived quality significantly influence brand extension attitude on Dettol and Lifebuoy. Consumer innovativeness significantly influence brand extension attitude on Dettol and Lifebuoy. The results of F test forDettol and Lifebuoy indicates brand knowledge, perceived quality and consumer innovativeness simultanously influence brand extension attitude. Keywords: brand knowledge, perceived quality, consumer innovativeness, brand extension attitude